(4b-5c)+(5a+2b)=

Simple and best practice solution for (4b-5c)+(5a+2b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4b-5c)+(5a+2b)= equation:


Simplifying
(4b + -5c) + (5a + 2b) = 0

Remove parenthesis around (4b + -5c)
4b + -5c + (5a + 2b) = 0

Remove parenthesis around (5a + 2b)
4b + -5c + 5a + 2b = 0

Reorder the terms:
5a + 4b + 2b + -5c = 0

Combine like terms: 4b + 2b = 6b
5a + 6b + -5c = 0

Solving
5a + 6b + -5c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6b' to each side of the equation.
5a + 6b + -6b + -5c = 0 + -6b

Combine like terms: 6b + -6b = 0
5a + 0 + -5c = 0 + -6b
5a + -5c = 0 + -6b
Remove the zero:
5a + -5c = -6b

Add '5c' to each side of the equation.
5a + -5c + 5c = -6b + 5c

Combine like terms: -5c + 5c = 0
5a + 0 = -6b + 5c
5a = -6b + 5c

Divide each side by '5'.
a = -1.2b + c

Simplifying
a = -1.2b + c

See similar equations:

| w/22+22=44 | | -3(5n-5)=-5n-15 | | x^4+x^3-23x^2+3x+90=0 | | A=7B+5C | | -2=r-(5) | | z/2=z+1/3 | | -3-5/-4+(2-1) | | 4x=238 | | 72+5=9z+3 | | (6x^2+5x+7)-(2x^2-11x+12)= | | 15p/2+p=17 | | -2y=-x+2 | | 6000(1+0.07)9= | | y=1/3x+2/5 | | 8=x-(1) | | 1/5(x+3)^2-5=0 | | -3/20x=6 | | x+4y=-5 | | -4x-4=5-(7x-6) | | 5y^2-y-1=0 | | x+(x-17.8)=196.8 | | 4x/9-5=x | | 5x+5-2x=3+4 | | x-(-4x)=x+9 | | 4x^2-32x+64=3x^2-12x-36 | | 5(6x-2)+3(8-3x)-5(4x+4)=-3 | | 7-4y=3 | | -5n-6(n-5)=85 | | p=21+sw | | 4+7y=3 | | y^2+4y-7=0 | | -2(2s-6)-12=-3(7s+0)-4 |

Equations solver categories